The role and novel use of natural killer cells in graft-versus-leukemia reactions after allogeneic transplantation - Hadjis, Ashley D.; McCurdy, Shannon R. (Frontiers in Immunology, 2024)
Allogeneic hematopoietic cell transplantation (HCT) has transformed over the past several decades through enhanced supportive care, reduced intensity conditioning (RIC), improved human leukocyte antigen (HLA) typing, and novel graft-versus-host disease (GVHD)-prevention and treatment strategies. Most notably, the implementation of post-transplantation cyclophosphamide (PTCy) has dramatically increased the safety and availability of this life-saving therapy. Given reductions in nonrelapse mortality (NRM) with these advances, the HCT community has placed even greater emphasis on developing ways to reduce relapse -the leading cause of death after HCT. When using RIC HCT, protection from relapse relies predominantly on graft-versus-leukemia (GVL) reactions. Donor lymphocyte infusion (DLI), adoptive cellular therapy, checkpoint inhibition, and post-HCT maintenance strategies represent approaches under study that aim to augment or synergize with the GVL effects of HCT. Optimizing donor selection algorithms to leverage GVL represents another active area of research. Many of these strategies seek to harness the effects of T cells, which for decades were felt to be the primary mediators of GVL and the focus of investigation in relapse reduction. However, there is growing interest in capitalizing on the ability of natural killer (NK) cells to yield potent anti-tumor effects. A potential advantage of NK cell-based approaches over T cellmediated is the potential to reduce NRM in addition to relapse. By decreasing infection, without increasing the risk of GVHD, NK cells may mitigate NRM, while still yielding relapse reduction through identification and clearance of cancer cells. Most T cell-focused relapse-prevention strategies must weigh the benefits of relapse reduction against the increased risk of NRM from GVHD. In contrast, NK cells have the potential to reduce both, potentially tipping the scales significantly in favor of survival. Here, we will review the role of NK cells in GVL, optimization of NK cell match or mismatch, and burgeoning areas of research in NK cell therapy such as adoptive transfer and chimeric antigen receptor (CAR) NK cells.